Groepsfoto genomen tijdens het "Sommertreffen" van "Kãmpfer und Freunde der Spanischen Republik 1936-1939" (2006)
Groepsfoto genomen tijdens het "Sommertreffen" van "Kãmpfer und Freunde der Spanischen Republik 1936-1939".